1995
DOI: 10.1007/bf00317276
|View full text |Cite
|
Sign up to set email alerts
|

Woody tissue maintenance respiration of four conifers in contrasting climates

Abstract: We estimate maintenance respiration for boles of four temperate conifers (ponderosa pine, western hemlock, red pine, and slash pine) from CO efflux measurements in autumn, when construction respiration is low or negligible. Maintenance respiration of stems was linearly related to sapwood volume for all species; at 10°C, respiration per unit sapwood volume ranged from 4.8 to 8.3 μmol CO m s. For all sites combined, respiration increased exponentially with temperature (Q =1.7, r=0.78). We estimate that maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
162
4
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(184 citation statements)
references
References 29 publications
12
162
4
6
Order By: Relevance
“…More information is also needed to be able to choose the best unit to scale up stem or branch respiration to stand level, because this unit can have a large impact on the final results. Hitherto, the most common units have been surface area [18,46] or sapwood volume [36], but sapwood fresh mass [49] or sapwood dry mass and nitrogen content [28,[37][38][39][40] have also been used to express maintenance respiration. Sprugel et al [43] suggested that sapwood volume was a better calculation base, because respiration rates per unit volume are rather constant within coniferous species.…”
Section: Introductionmentioning
confidence: 99%
“…More information is also needed to be able to choose the best unit to scale up stem or branch respiration to stand level, because this unit can have a large impact on the final results. Hitherto, the most common units have been surface area [18,46] or sapwood volume [36], but sapwood fresh mass [49] or sapwood dry mass and nitrogen content [28,[37][38][39][40] have also been used to express maintenance respiration. Sprugel et al [43] suggested that sapwood volume was a better calculation base, because respiration rates per unit volume are rather constant within coniferous species.…”
Section: Introductionmentioning
confidence: 99%
“…The point measurements were made with an open system (Field et al, 1991) and an ADC LCA3 or LCA4 gas analyzer with an air flow of 270 _amol/s. Methods are similar to those described in Ryan et al (1995) and are more fully described in Lavigne and Ryan (1997).…”
Section: Data Acquisition Methodsmentioning
confidence: 99%
“…Debido al efecto de la temperatura en la velocidad de las reacciones enzimáticas, la temperatura y la emisión de CO 2 están generalmente relacionadas de manera exponencial. En ocasiones, el grado de ajuste entre ambas variables es mayor cuando se considera la temperatura previa a la medida de emisión de CO 2 en lugar de la temperatura simultánea (Ryan et al 1995;figura 3). Este desfase temporal, que depende de la propia evolución de la temperatura del tronco a lo largo del día, podría estar ligado a la resistencia al flujo radial de CO 2.…”
Section: Resistencia Al Flujo Radial De Counclassified
“…yor es el intervalo temporal para un mejor ajuste entre la emisión de CO 2 y la temperatura, mayor es la resistencia al flujo radial de CO 2 . En ocasiones este desfase es de varias horas (Ryan et al 1995, Maier y Clinton 2006, hecho que sugiere que el CO 2 tarda varias horas en atravesar el tronco y liberarse a la atmósfera, y es coherente con los rangos de resistencia a la difusión observados por Steppe et al (2007). No obstante, la anomalía en la relación entre el flujo radial de CO 2 y la temperatura también podría corresponderse con otros fenómenos, como el transporte de CO 2 en el flujo de savia (McGuire y Teskey 2002, Hölttä y Kolari 2009, Tarvainen et al 2014, descrito en la sección siguiente.…”
Section: Resistencia Al Flujo Radial De Counclassified
See 1 more Smart Citation